2019
DOI: 10.1186/s13014-019-1382-1
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic ablative radiotherapy versus conventionally fractionated radiotherapy in the treatment of hepatocellular carcinoma with portal vein invasion: a retrospective analysis

Abstract: BackgroundThis study aimed to compare the clinical outcomes of stereotactic ablative radiotherapy (SABR) and conventionally fractionated radiotherapy (CFRT) in hepatocellular carcinoma (HCC) patients with portal vein invasion (PVI).MethodsHCC patients with PVI treated with radiotherapy from 2007 to 2016 were analysed. CFRT was administered at a median dose of 51.5 Gy (interquartile range, 45–54 Gy) with 1.8–3 Gy per fraction. SABR was administered at a median dose of 45 Gy (interquartile range, 40–48 Gy) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…Our results in both groups compared favorably to the published literatures [12][13][14][15][16][17][18][19][20][21] (Table 2). The comparability of PFS and OS in our study may be because the therapeutic effect is actually the same, and not the arti cial result of particularly poor or excellent IMRT and SBRT procedures.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our results in both groups compared favorably to the published literatures [12][13][14][15][16][17][18][19][20][21] (Table 2). The comparability of PFS and OS in our study may be because the therapeutic effect is actually the same, and not the arti cial result of particularly poor or excellent IMRT and SBRT procedures.…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, Rim et al [22] reported a comparable 1-year OS between 3-dimensional conformal RT and SBRT (48.5% vs 46.5%). Yang et al [18] also showed a considerable survival bene t in SBRT compared to RT (1-and 2-year OS: 33.1% and 16.5% vs. 17.3% and 5.2%) in 140 patients with advanced HCC with PVTT. Consequently, it is plausible that SBRT is feasible for patients with PVTT, with acceptable toxicity and survival outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…Currently, SBRT has been used in the treatment of HCC with PVTT [ 16 , 17 ]. To shrink the tumour thrombus and maintain sufficient portal venous flow, SBRT is recommended for patients with unresectable HCC having PVTT and for those with contraindications for TACE [ 18 , 19 ]. Despite the existence of clinical reports on the efficacy and safety of SBRT for HCC with PVTT, to the best of our knowledge, there is no nomogram for predicting survival of patients with HCC and PVTT after undergoing SBRT.…”
Section: Introductionmentioning
confidence: 99%
“…Their reported survival rate is lower than the 1-year OS of around 66% for our subgroup of patients treated with BED ≥80 Gy. However, of note is that they used a lower BED and all of their patients had tumor vascular thrombosis, which may have contributed to inferior outcomes (17).…”
Section: Discussionmentioning
confidence: 99%